Manajemen Pembiayaan Pendidikan Masa Pandemi Covid-19 di SMK Gazza Wiguna 1 - Siti Waliyah; Siti Hadiyanti Dini; Ahmad Syarif (Transformasi Manageria: Journal of Islamic Education Management, 2021)
This research is motivated by the Covid 19 pandemic which has changed the system in the world, especially in the education sector. The Covid 19 pandemic has greatly affected the world economy, including in Indonesia. The purpose of this study was to determine the management of education financing at Gazza Wiguna 1 Vocational High School before the Covid 19 pandemic and during the Covid 19 pandemic and to determine the impact of the pandemic on the financing at Gazza Wiguna Vocational High School 1. This study used a qualitative descriptive approach by examining the facts that occurred. . The research was conducted at SMK Gazza Wiguna 1 Kab. Bogor. The data collection technique used was the interview that came from the head of SMK Gazza Wiguna 1, the Deputy Head of the School, the treasurer of SMK Gazza Wiguna 1 and the parents of the students. Funding management at SMK Gazza Wiguna includes planning, management, implementation and supervision, focusing on the needs of schools, teachers and students. The Covid 19 pandemic has an impact on the management of education financing at the Gazza Wiguna 1 Vocational High School, namely on hiring teachers. Where during normal conditions, SMK Gazza Wiguna 1 relies on tuition fees to honor teachers, while during the Covid 19 pandemic, many students had difficulty paying tuition fees so that Gazza Wiguna 1 Vocational School made a budget rotation so that they could continue to honor teachers.